Determinants of Microfinance Adoption, Challenges Encountered, and Principal Solutions: An Empirical Analysis Using Theory of Planned Behaviour - Magar, Sushma; Basyal, Devid Kumar; Lawaju, Purnima; Paudel, Udaya Raj; Poudel, Devi Kumari (Journal of Innovation in Academia, 2023)
Microfinance refers to the provision of financial services to low-income individuals and businesses, serving as a financial tool to reduce poverty and provide financial support to low-income groups. This study aims to determine the factors influencing customers’ intentions towards microfinance in Kathmandu Valley. The study employs an explanatory research design in conjunction with the Theory of Planned Behavior framework. Primary data from 303 respondents were collected using the KOBO toolbox. Purposive sampling, a non-probability sampling technique, was employed for data collection. Descriptive and inferential data analysis was carried out using MS-Excel and SMART PLS 4.0. The majority of respondents consisted of married middle-aged women actively engaged in their own business ventures. Common challenges encountered by microfinance customers included high-interest rates, insufficient security, and limited financial knowledge. The principal solutions identified included the establishment of robust microfinance policies, the integration of innovation and new technologies, the provision of financial training, and the facilitation of enhanced loan repayment strategies. The study revealed that, among the three primary factors examined, both subjective norms and perceived behavioral control had a significant impact on customers’ intentions to adopt microfinance. On the other hand, attitude was found to have an insignificant impact on customers’ intentions to embrace microfinance. The findings of this study suggest that microfinance can be a valuable tool for poverty reduction and financial inclusion. However, it is important to address the challenges that microfinance customers face in order to maximize its potential impact. The solutions identified in this study can help make microfinance more accessible and affordable for low-income individuals and businesses.